FILOSOFI DAN PERWUJUDAN PRINSIP TAUHȊDULLAH DAN AL-‘ADALAH, DALAM IJARAH, DAN IJARAH MUNTAHIA BI-TAMLIK (IMBT) - M. E. Burhanudin (IAIN Ambon, 2018)
This paper describes about the philosophy and the embodiment prinsisp of Tauhȋdullah and al-‘adalah in ijarah and Ijarah Muntahia Bi-Tamlik (IMBT). In this paper will have the discussion on the definition of the principles put forward tauhȋdullah and al-‘adalah, the explanation of ijarah, Ijara Muntahia Bi-Tamlik (IMBT), the embodiment of the principle of ijarah and ijarah Tauhȋdullah Muntahia Bi-Tamlik (IMBT), the embodiment of the principle of al-ijarah and Ijarah Muntahia Bi-Tamlik (IMBT). And concluded that tauhȋdillah principle as a principle which provides binding rules between man and his lord, and al-‘adalah principle as a principle that will make an impact of harmony to human being, as with the values of justice there will be no party who feel aggrieved or oppressed. So as to understand the Tauhȋdillah embodiment in ijarah and ijarah Muntahia Bi-Tamlik (IMBT) then the system of ijara and IMBT will be applied correctly in accordance with Islamic law.